2022
DOI: 10.1038/s41598-021-03968-4
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal whole-body energy metabolism in iron-deficient humans despite preserved skeletal muscle oxidative phosphorylation

Abstract: Iron deficiency impairs skeletal muscle metabolism. The underlying mechanisms are incompletely characterised, but animal and human experiments suggest the involvement of signalling pathways co-dependent upon oxygen and iron availability, including the pathway associated with hypoxia-inducible factor (HIF). We performed a prospective, case–control, clinical physiology study to explore the effects of iron deficiency on human metabolism, using exercise as a stressor. Thirteen iron-deficient (ID) individuals and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“… 54 , 55 , 56 The divergence in findings have been explained, at least in part, by a recent prospective case control study, which demonstrated that although non‐anaemic iron‐deficient individuals treated with intravenous iron showed no differences in both aerobic respiration and VO 2 max, intravenous iron increased lactate threshold during exercise, implying an increased ability to generate work aerobically with increasing exercise intensities in the absence of fatigue. 57 These findings are in keeping with previous physiological experiments in animals with clinical implications. 13 Further research investigating changes in lactate concentration in iron‐deficient individuals treated with intravenous iron is needed to confirm this.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 54 , 55 , 56 The divergence in findings have been explained, at least in part, by a recent prospective case control study, which demonstrated that although non‐anaemic iron‐deficient individuals treated with intravenous iron showed no differences in both aerobic respiration and VO 2 max, intravenous iron increased lactate threshold during exercise, implying an increased ability to generate work aerobically with increasing exercise intensities in the absence of fatigue. 57 These findings are in keeping with previous physiological experiments in animals with clinical implications. 13 Further research investigating changes in lactate concentration in iron‐deficient individuals treated with intravenous iron is needed to confirm this.…”
Section: Discussionsupporting
confidence: 89%
“…Impact of intravenous iron on muscle function and performance has demonstrated a mix of results, with studies reporting both increases 22,24,53 and no change in exercise capacity in response to iron therapy 54–56 . The divergence in findings have been explained, at least in part, by a recent prospective case control study, which demonstrated that although non‐anaemic iron‐deficient individuals treated with intravenous iron showed no differences in both aerobic respiration and VO 2 max, intravenous iron increased lactate threshold during exercise, implying an increased ability to generate work aerobically with increasing exercise intensities in the absence of fatigue 57 . These findings are in keeping with previous physiological experiments in animals with clinical implications 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This leads to reduced iron supply into plasma by blocking the absorption of dietary iron in the duodenum, iron recycling in macrophages and the release of body iron stores (Xiao et al 2020). Iron deficiency (ID) in athletes has been shown to reduce endurance capacity and athletic performance through altered energy metabolism, decreased lactate threshold, early onset of fatigue and worsened test times (Hinton 2014;Frise Communicated by Klaas R westerterp.…”
Section: Introductionmentioning
confidence: 99%
“…However, this population also exhibits a considerable prevalence of ID and IDA, especially in women (Hinton, 2014;Pedlar et al, 2018;Sim et al, 2019). Iron deficiency in athletes has been shown to reduce endurance capacity and athletic performance through altered energy metabolism, decreased lactate threshold, early onset of fatigue and worsened test times (Frise et al, 2022;Hinton, 2014). Furthermore, ID may negatively There are many factors that determine the regulation of iron homeostasis in women athletes (Pedlar et al, 2018), which often makes maintaining a healthy iron status a challenge for female athletes and their coaches, nutritionists, and clinicians.…”
Section: Postmenopausal Stage Late Perimenopausal Stagementioning
confidence: 99%
“…This leads to reduced iron supply into plasma by blocking the absorption of dietary iron in the duodenum, iron recycling in macrophages and the release of body iron stores (Xiao et al, 2020). Iron deficiency in athletes has been shown to reduce endurance capacity and athletic performance through altered energy metabolism, decreased lactate threshold, early onset of fatigue and worsened test times (Frise et al, 2022;Hinton, 2014). Furthermore, ID may negatively impact athletes' health and well-being, by affecting different domains of cognitive performance such as motivation, concentration and decision making (Pedlar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%